2007
DOI: 10.2174/092986707782023622
|View full text |Cite
|
Sign up to set email alerts
|

Antiangiogenic Agents: an Update on Small Molecule VEGFR Inhibitors

Abstract: Angiogenesis is a tightly regulated process that leads to the formation of new blood vessels sprouting from pre-existing microvasculature and occurs in limited physiological conditions or under pathological situations such as retinopathies, arthritis, endometriosis and cancer. Blockade of angiogenesis is an attractive approach for the treatment of such diseases. Particularly in malignancies, antiangiogenic therapy should be less toxic in comparison with conventional treatments such as chemotherapy, as angiogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
62
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 135 publications
(199 reference statements)
0
62
0
Order By: Relevance
“…VEGFR-2 cellular potency was further improved to submicromolar levels by substituting a pyridine central core for the benzene ring. Structure-activity relationship trends similar to the benzo [1,3]dioxol-5-yl subseries were also observed within the 2,3-dihydro-benzo-[1,4]dioxin-6-yl subclass (compare 9-13 to 14, 16, and 18-20, respectively). Heterocyclic groups other than the 4-pyridyl moiety likewise showed dual kinase/tubulin activity within the 2,3-dihydro-benzo [1,4]dioxin-6-yl subclass (imidazolyl 21 and quinolinyl 23).…”
mentioning
confidence: 58%
See 4 more Smart Citations
“…VEGFR-2 cellular potency was further improved to submicromolar levels by substituting a pyridine central core for the benzene ring. Structure-activity relationship trends similar to the benzo [1,3]dioxol-5-yl subseries were also observed within the 2,3-dihydro-benzo-[1,4]dioxin-6-yl subclass (compare 9-13 to 14, 16, and 18-20, respectively). Heterocyclic groups other than the 4-pyridyl moiety likewise showed dual kinase/tubulin activity within the 2,3-dihydro-benzo [1,4]dioxin-6-yl subclass (imidazolyl 21 and quinolinyl 23).…”
mentioning
confidence: 58%
“…8 This work demonstrated that a trifluoromethyl group in the meta position in compound 1 or benzo [1,3]dioxol-5-yl functionality in triazole 4 results in an inhibitory activity in the VEGFR-2 enzymatic assay (Table 1). Moreover, triazole 1 along with several other analogues (not shown) exhibited VEGFR-2 activity around 1 μM in the cellular phosphorylation assay.…”
mentioning
confidence: 94%
See 3 more Smart Citations